Bridging the first step: special educators, routines, and predictable transitions to school for children with ASD in Norway - Tøhaug, Tonje; Lefstad, Kristine Tyldum; Page, Alexander Gamst; Storås, Marianne Hatlem; Chahboun, Sobh (Frontiers in Education, 2025)
IntroductionThe transition from kindergarten to school is a major developmental milestone for all children, and it is particularly demanding for children with Autism Spectrum Disorder (ASD) due to their heightened need for structure, predictability, and emotional security. This study investigates how special educators in one Norwegian municipality facilitate this transition, emphasizing continuity in routines, collaboration, and pedagogical strategies that support children with ASD.MethodsA qualitative research design was employed, consisting of eight in-depth interviews with special education teachers from four different institutions in the municipality. The interviews gathered diverse professional perspectives on transition practices, challenges, and collaborative processes.ResultsFindings reveal that early planning, systematic familiarization through visit days, and continuity in daily routines are essential in fostering predictability and emotional security for children with ASD. Interdisciplinary and inter-agency collaboration—including kindergartens, schools, Educational-Psychological Services (PPT), and parents—plays a critical role in ensuring tailored support and cohesive transition processes. Key challenges include limited time, lack of formalized routines, and resource constraints, which can hinder the implementation of individualized measures. Despite these obstacles, flexible adaptations, early initiation of transition routines, and strong parental involvement were found to significantly improve the transition experience.DiscussionThe study contributes to the field of special education by identifying effective practices that promote inclusive, predictable, and emotionally secure transitions for children with ASD. The findings have important implications for policy development, professional practice, and future research, particularly regarding the need for formalized procedures, sufficient resources, and strengthened collaboration across institutions.